POTENTIAL OF Arcangelisia flava AS ANTIHYPERURICEMIA THERAPY: LITERATURE REVIEW - Amanda, Ajeng Intan Estri; Salni; Ziske Maritska; Fatmawati (Majalah Kedokteran Sriwijaya, 2024)
This study is a literature review that aims to evaluate the potential of Arcangelisia flava (A. flava) as an anti-hyperuricemia therapy. Hyperuricemia is a condition that is closely related to several diseases, such as obesity, diabetes, hypertension, and cardiovascular disease. As the final product of purine conversion catalyzed by the enzyme xanthine oxidase (XO), Uric acid is an essential focus in managing hyperuricemia. In vitro test results show that ethanol extract from yellow wood leaves and roots has the potential to inhibit the activity of the XO enzyme, thereby reducing the formation of uric acid. Although yellow wood is traditionally known in herbal medicine, more in-depth scientific information is still needed, especially in the context of anti-hyperuricemia therapy, which is still limited in clinical studies. This review study aims to present a comprehensive overview of research related to the use of A. flava in anti-hyperuricemia therapy, with the hope of providing a better understanding of this plant's potential in treating this condition.